Targeting Benefits Governance and Eligibility Criteria for Work Protection and Poverty Reduction Policy Process in COVID-19 era - Eddy Bruno Esien (Yayasan Ilomata, 2022)
This paper analyses eligibility criteria in der realms of public and social assistance programs under targeting benefits governance to enable third-country immigrants work protection and poverty reduction in Austria, Finland, and the Czech Republic's COVID-19 era. Existing research pointed to the COVID-19 pandemic social disorder that confronts policymakers under intense budgetary pressure and increasing out-of-work population to shift on assisting the unemployed from universal to selective targeting benefits that stress public resources distribution on a measure of financial need to the poor instead of unlimited transfer to the entire population as social rights. However, targeting governance is imperative to challenges in terms of equity and efficiency. Based on a qualitative cross-national case-oriented research approach, documents are collected and analyzed with documents and content analysis techniques to fill the gap. The findings indicate that conditional age segmentation, legislative behavioral requirement, and functional impairment regulative tools influence targeting welfare benefits eligibility governance with a lack of solidarity and transparency that may impair public and social assistance to manage third-country immigrants' work protection and poverty reduction in COVID-19 era settings. However, the comparative entities' determination of targeting benefits level differs in Austria (regional), Finland (national), and Czechia (national). The outcome indicates a new paternalism and reciprocity approach in times of austere redistributive politics. It is relevant because it reflects enabling state neo-liberal social protection system, which not only heightens means-tested selectivity and targets individual responsibilities but tactfully raises the eligibility threshold that may undermine minority group's belongings and social cohesion, participatory democracy, and equitable development in COVID-19 era.